Examining engaged couples’ opinions and attitudes towards fertility awareness, family planning and parenting in terms of gender - Özcan, Ebru; Topatan, Serap (Informa UK Limited, 2022)
Being a parent that is part of the social life of individuals and getting married should be evaluated together with fertility to improve the health of society. Because individuals who are unaware of fertility may tend to make wrong decisions about how to manage their reproductive abilities. This study was conducted to determine by gender difference the fertility awareness of engaged couples and their attitudes toward parenthood and family planning. This cross-sectional study included 504 people who had decided to marry. In this study, a male/female questionnaire developed by the researcher and the Family Planning Attitudes Scale were used. When the couples evaluated the importance of having children to them on a scale from 0 to 10, no statistically significant differences by gender could be found (p = .589). Among the criteria for having children, the rate of agreement with the condition of having sufficient economic strength was higher among women than men (p = .031). The rate of agreement with the conditions of reaching a certain level of expertise in one’s occupation (p = .014) and living in a big enough house (p = .040) was higher among men than women. The Family Planning Attitudes Scale total mean score was 112.5 for the male participants and 117.0 for the female participants (p = .004). The scale evaluates the family planning attitude as positive and negative. Higher scores indicate more positive attitudes toward family planning. It was determined that couples’ were at a similar level of fertility awareness and women had a more positive family planning attitude than men. There were differences by gender in couples’ views on parenting.
Keywords: 5. Gender equality